Stropharia acanthostipitata (Agaricales, Strophariaceae), a new species from Tropical America - Vizzini, Alfredo; Angelini, Claudio; Cheype, Jean-Louis; Battistin, Eliseo; Ercole, Enrico (Phytotaxa, 2017)
A new species, Stropharia acanthostipitata, is here described from the Dominican Republic and French Guiana based on morphological and molecular ITS/LSU analyses. It is distinguished by a dry, smooth and hygrophanous pileus with minute and fugacious velar remnants at the pileus margin, exannulate stipe, brown lamellae, presence of chrysocystidia on both edge and face of lamellae, and the occurrence of acanthocytes all over the stipe surface.